DESIGN AND THERMAL ANALYSIS OF PISTON - SANTHOSH, TUMPALA UMA (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
This project mainly deals with the design and analysis of piston. Piston is a component of reciprocating engines, reciprocating pumps, gas compressors and pneumatic cylinders among other similar mechanisms. In an engine, its purpose is to transfer force from expanding gas in the cylinder to the crankshaft via a piston rod and/or connecting rod. Here the piston is designed and analysis has been studied. Piston temperature has considerable influence on efficiency, emission, performance of the SI engine. Purpose of the investigation is measurement of piston transient temperature at several points on the piston, from cold start to steady condition and comparison with the results of finite element analysis. In this project the piston is modeled and assembled with the help of CATIA software and the component is meshed and analysis is done in ANSYS software and the thermal and static behavior is studied and the results are tabulated. The various stresses acting on the piston under various loading conditions has been studied. Coupled field analysis (i.e) structural + thermal is done on the piston to verify the strength. The analysis is done using two different materials Aluminum-boron and Aluminium-5045. Comparison is done for the two materials to verify the better material for our designed piston. In the preset, thesis work has been taken up on the following aspects to cover the research gaps and to present the results based on the systematic studies : • Temperature distribution and heat flow through the piston of an engine. • FEA analysis of the piston to measure temperature at the points where it is not possible to find out practically and to observe the heat flow inside the piston